THE HEALTH IMPLICATIONS OF HUMAN TRAFFICKING IN NIGERIA - J.E. , IBEAGHA; L. , ANANOMO; N.E., IBEAGHA (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Human trafficking is aphenomenon that is currently generating a lot of concern globally, especially in countries like Nigeria. the vulnerability ofprospective victims are exploited in many respects: the victims most of whom arepre-teens, teenagers and mostly females are taken away from their home lands to cities within their country or across national boundaries and exploitedfor optimum economic benefits. Many of them are engaged in cheap labour such as domestic servants, beggars, commercial sex workers or put into otherforms of servitude akin to slavery. All these are done to the victims to the detriment of their health. This paper x-rayed the phenomenon, its trends in Nigeria, motivations for trafficking in Nigeria, health implications, ways of combating the evil and finally recommendations for addressing the problem.